Variations in prevalence of diabetes in various occupations: a quantitative and qualitative review - Naveena, T. (International Journal Of Community Medicine And Public Health, 2016)
Diabetes is one of the most dangerous diseases associated with many comorbidities and mortalities in world. This is associated with different risk factors and its occurrence cannot be predicted. The several risk factors include family history, overweight, unhealthy diet, sedentary lifestyle, increasing age, high blood pressure, stress. Prediction of occurrence and worsening of diabetes cannot be made but our duty is to reduce the risk factors to prevent ourselves landing up in such a long-lasting life burdening disease. Occupation determines many of the risk factors like lifestyle and stress factors as they are more or less similar to everyone belonging to a particular occupation. Study on occupational prevalence of diabetes helps us to identify our risk of diabetes and to prevent it. But presently unfortunately there are only 6 articles available on the occupational prevalence of diabetes. They report that there is increased prevalence of diabetes in police personnel and decreased prevalence of diabetes in farmers and construction workers. Though there is an article available on occupational prevalence of diabetes in teachers, conclusions cannot be drawn as the controls were not included in the study. So there is an immediate requirement to conduct research on prevalence of diabetes in various occupations by including controls.